2000
DOI: 10.1007/bf02236856
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of peritoneal lavage with antiseptics in prevention of recurrent colorectal cancer caused by tumor-cell seeding

Abstract: Povidone-iodine toxicity proved to be a major issue in vivo. However, povidone-iodine low molecular weight 1 percent was safe when used for short periods and very effective when a limited number of tumor cells was inoculated. The use of cytotoxic agents to prevent recurrent disease caused by tumor cell seeding in patients seems to make sense only when the "inoculum size" of exfoliated or soiled cancer cells is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…It is debatable whether these results can be extrapolated to the situation of an exfoliated cell deposited on and anchored to a substratum of extracellular matrix, given that the activity of cytotoxics in vivo is greatly limited by their chemical inactivation by organic molecules. [14][15][16] This study is the first to examine the efficacy of cytotoxic agents on cell monolayers, with plastic and extracellular matrix substrata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is debatable whether these results can be extrapolated to the situation of an exfoliated cell deposited on and anchored to a substratum of extracellular matrix, given that the activity of cytotoxics in vivo is greatly limited by their chemical inactivation by organic molecules. [14][15][16] This study is the first to examine the efficacy of cytotoxic agents on cell monolayers, with plastic and extracellular matrix substrata.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] In contrast, the physical (osmotic) rather than chemical cytotoxicity of water may confer advantages over other agents. First, water is not subject to chemical alteration by organic peritoneal secretions as observed with antiseptic lavage preparations, and second, whereas eukaryotic cells exhibit a wide variability in their sensitivity to different chemical agents, they are universally susceptible to osmotic stress.…”
mentioning
confidence: 88%
“…Other substances, such as chlorhexidine–cetrimide preparations and povidone–iodine, have shown promising results in vitro , but were unsuccessful in vivo 37, 38. The weak cytotoxic effect in vivo may be the result of chemical inactivation by organic molecules in peritoneal fluid and blood38–40. The antiangiogenic agent suramin appeared to enhance tumour growth in an animal model, possibly owing to an unexpected immunosuppressive effect31.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels were monitored in five cases and showed only a rise in serum iodine and thyroxine levels during 24-hour follow-up, and then returned to near the preoperative levels by 72 hours. With a goal to eradicate intraperitoneal exfoliated cancer cells, in a rat model, Basha et al 74 found that 2 percent PVI caused death in all rats, whereas 1 percent PVI was safe and effective. They concluded that PVI in no greater strength than 1 percent could be used in clinical practice.…”
Section: Safety and Adverse Effectsmentioning
confidence: 97%